2012
DOI: 10.1002/ange.201203795
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Nanostructures from the Self‐Assembly of Designed Repeat Protein Modules

Abstract: Superhelicale Filamente, die aus einer einzigen Proteinkette bestehen, können ausgehend von monomeren Repeat‐Proteinen durch Kontrolle der chemischen Eigenschaften der terminalen Grenzflächen erhalten werden. Das Assoziat wurde in wässriger Lösung bei neutralem pH‐Wert und Raumtemperatur gebildet, und die Module waren rekombinant hergestellte Tetratricopeptid‐Repeat‐Proteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…[29][30][31][32] We have recently used these modules to show the specific functionalization of patterned polymeric surfaces. [33,34] Moreover, it has been shown that under certain conditions CTPR proteins self-assemble into ordered structures including ordered protein films comprised, [35] and linear nanofibers in solution [36,37], mimicking the packing observed in the crystal forms of CTPRs. [27,28,38] These results illustrate the potential of these protein modules as self-assembling building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] We have recently used these modules to show the specific functionalization of patterned polymeric surfaces. [33,34] Moreover, it has been shown that under certain conditions CTPR proteins self-assemble into ordered structures including ordered protein films comprised, [35] and linear nanofibers in solution [36,37], mimicking the packing observed in the crystal forms of CTPRs. [27,28,38] These results illustrate the potential of these protein modules as self-assembling building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…A protein with a pair of binding partners on opposite sides would polymerize controllably in a manner depending on the nature of the binding partners. This strategy has been used previously [16][17][18][19][20][21][22][23] , but there remained several problems: for example, chemical modifications of monomers to make binding sites are often necessary [16][17][18][19][20] , single strands of the polymers are supposed to break easily and to be not stable for long periods in dilute solution because they are held together by noncovalent interactions 16,17,[21][22][23] , and single strands of the polymers often assemble in an uncontrolled manner 21,22 .…”
mentioning
confidence: 99%
“…In particular, we have incorporated the ability to fit and simulate equilibrium unfolding experiments with user defined protein topologies, using a matrix formulation of the 1-D heteropolymer Ising model. This aspect of PyFolding will be of particular interest to groups working on protein folds composed of repetitive motifs such as Ankyrin repeats and tetratricopeptide repeats, given that these proteins are increasingly being used as novel antibody therapeutics (38)(39)(40)(41) and biomaterials (42)(43)(44)(45)(46)(47). Further, as analysis can be performed in Jupyter notebooks, it enables novice researchers to easily use the software and for groups to share data and methods.…”
Section: Discussionmentioning
confidence: 99%